Early Childhood: Motor Comparison of Breastfed and Formula-fed Children Aged 4-6 Years - Nurhayati, Nurhayati; Ramli, Ramli (Indonesian Journal of Early Childhood Education Studies, 2021)
The study aims to see the comparisons and differences in motor skills of breastfed and formula-fed children aged 4-6 years both in fine and gross motor. The approach used is descriptive quantitative by looking at comparisons or differences in children's motoric development. The subjects in this study are 40 children consuming breast milk aged 4-6 years and 40 children consuming formula milk aged 4-6 years, so a total of participants are 80 children with parents as respondents and the results are significant. The findings show that children consuming breast milk are better and faster in fine motor and gross motor development than children consuming formula milk.